Quantification and modeling of ankle biomechanical characteristics - Musalimov, V.M.; Perepelkina, S.Yu; Paasuke, M.A.; Gapeeva, E.N.; Ereline, J.J.; Erofeev, M.A. (Nauchno-tekhnicheskiĭ vestnik informat͡s︡ionnykh tekhnologiĭ, mekhaniki i optiki, 2024)
Calculation method for ankle joint biomechanical characteristics is developed: gear relation, ankle joint rigidity, foot inertia moment. The basis of research is the experimental data on flexion-extension-rotation movement of ankle joint and foot walking reaction obtained in the laboratory of kinesiology and biomechanics of the Tartu University, Estonia. Conservation principles of angular momentum were used for foot inertia moments calculation. Angular momentum was calculated according to foot reaction and further estimation of reactive force impulse data. The free transfer dynamics method (FTD-method) was suggested that allowed assessing ankle joint rigidity. Ankle joint gear relation has been calculated for the first time. Foot inertia moments in reference to two ankle joint axes have been calculated on the basis of foot reaction experimental data and angular movement markers data. Experimental data in the phases of foot transfer with further foot movement modeling in this phases have been used in order to assess ankle joint rigidity. Practical relevance of this research is defined by the perspective of further researches and experiments, for example, with the usage of inertial sensors for personalized walk data assessment for patients with remote condition monitoring and information transfer to rehabilitation centers. The given assessments of angle joint rigidity are useful for biomechatronic systems engineering.